Adult rat bones maintain distinct regionalized expression of markers associated with their development. - Simon C F Rawlinson; Ian J McKay; Mandeep Ghuman; Claudia Wellmann; Paul Ryan; Saengsome Prajaneh; Gul Zaman; Francis J Hughes; Virginia J Kingsmill (PLoS ONE)
The incidence of limb bone fracture and subsequent morbidity and mortality due to excessive bone loss is increasing in the progressively ageing populations of both men and women. In contrast to bone loss in the weight-bearing limb, bone mass in the protective skull vault is maintained. One explanation for this could be anatomically diverse bone matrix characteristics generated by heterogeneous osteoblast populations. We have tested the hypothesis that adult bones demonstrate site-specific characteristics, and report differences at the organ, cell and transcriptome levels. Limb bones contain greater amounts of polysulphated glycosaminoglycan stained with Alcian Blue and have significantly higher osteocyte densities than skull bone. Site-specific patterns persist in cultured adult bone-derived cells both phenotypically (proliferation rate, response to estrogen and cell volumes), and at the level of specific gene expression (collagen triple helix repeat containing 1, reelin and ras-like and estrogen-regulated growth inhibitor). Based on genome-wide mRNA expression and cluster analysis, we demonstrate that bones and cultured adult bone-derived cells segregate according to site of derivation. We also find the differential expression of genes associated with embryological development (Skull: Zic, Dlx, Irx, Twist1 and Cart1; Limb: Hox, Shox2, and Tbx genes) in both adult bones and isolated adult bone-derived cells. Together, these site-specific differences support the view that, analogous to different muscle types (cardiac, smooth and skeletal), skull and limb bones represent separate classes of bone. We assign these differences, not to mode of primary ossification, but to the embryological cell lineage; the basis and implications of this division are discussed.